Effects of exercise in cool versus hot conditions on pathways of gut permeability, systemic inflammation, and iron homeostasis in female athletes - Lucernoni, K. M.; Chacon, S. J.; Wiedenfeld Needham, K.; Halliwill, J. R.; Minson, C. T. (Physiological Reports, 2026)
Abstract The purpose of this study was to examine the time course and magnitude of the inflammatory, hepcidin and endotoxin responses evoked by exercise under hot environmental conditions in female athletes. In a randomized cross*over study design, 13 endurance trained female athletes (age 26 (range: 20-42) years; VO 2 max 57.7 (53.4, 62.1) mL·kg -1 ·min -1 ; mean (95% CI)) completed two exercise sessions on a treadmill at 70% VO 2 max in hot (35°C and 40% RH) and cool (11°C and 40% RH) environmental conditions. Peak body core temperature during the hot condition was greater than the cool condition (change +2.1°C (1.8, 2.3); +1.0°C (0.8, 1.3); p < 0.01). There were no changes in LPS or TNF- concentrations at any time point. The hot condition had a greater rise in IL-6 concentration at 1 h post exercise (hot: 1.6 pg/mL (1.0, 2.2); cool: 1.0 pg/mL (0.8, 1.3); p = 0.04). Hepcidin concentrations at 3 h post exercise were greater in the hot condition (hot: 15.1 ng/mL (8.8, 21.3); cool: 7.9 ng/mL (3.5, 12.2); p = 0.03). These data suggest that moderate exercise in a hot environment evokes a greater IL-6 concentration and hepcidin concentration post exercise than a cool environment without influence of gut permeability.